Fatigue and Hepatitis C: a focus group study - Christina Spataro; Sophie Afdhal; Ali A. Weinstein; Carey Escheik; Patrick Austin; Kathryn Brodie; Lynn Gerber; Zobair M. Younossi (Qualitative Research in Medicine & Healthcare)
Fatigue is often undiagnosed by health professionals as it is still seen as a nonspecific symptom without standard evaluations and effective treatments. Fatigue is present across many different diseases and has a profound effect on the quality of life of patients. However, it is still difficult to measure because of the lack of specificity of currently used self-report instruments. Patients with chronic hepatitis C infection, (HCV), experience fatigue as one of the most debilitating symptoms. The purpose of this study was to explore the types and dimensions of fatigue experienced by patients with HCV, identify specific terms they use to describe fatigue and assess how it influences everyday activities. Sixteen individuals with HCV (56% female, aged 58.1 ± 3.7 years) participated in three focus group sessions. The focus group sessions lasted between 60 and 90 minutes and were digitally recorded via audiotapes. Recorded focus groups’ audiotapes were analyzed through thematic analyses. The analysis suggested two primary categories of fatigue experiences. These were: capacity and engagement in activity. Capacity refers specifically to an individual’s sense of how much energy they have to do life activities or their maximum ability to produce energy. The word energy is the ability to perform work and includes one’s ability to access or utilize, expend, and restore it. The phrase engagement in activity, comprised two domains: initiation (getting started or being motivated) and personal satisfaction (value of the activity). This investigation helped to identify important domains of fatigue experienced by those with HCV. The findings augment our current understanding of fatigue for this group because the domains of fatigue and the terms used to describe it are not commonly represented in the most frequently used fatigue assessments.